HUBUNGAN KARAKTERISTIK SISWA DAN ORANGTUA DENGAN STATUS GIZI SISWA SEKOLAH DASAR NEGERI KB 4 KOTA BANJARMASIN - Mahdayani Lesda; Mochamad Rachmat; Sutanto Priyo Hastono (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2006)
Background: Several studies showed that among students at elementary school, undernutrition and overnulrition are still a nutrition problem. It was reported that undernutrilion among school students is 35% and 25% for male and female, respectively. However, the prevalence of overnulrition is 9% and 11% for male and female respectively. Objective: To analyze the association between student characteristics, parent characteristics, and nutritional status of student at public elementary school, namely KB4 in Banjarmasin city. Methods: The school was chosen because it was a pilot school in this city. Students selected purposively in grade IV, V, and VI so that the total of students was 190. The nutritional status assessed and catagorized using WAZ of WHO-NCHS standard. Results: The study indicated that prevalence of undeiweight was 20.5%. There was a significant association between nutrition status and having daily breakfast, mother's educational level, mother's nutrition knowledge, and parent's income. While purchase food at school jajan, student's nutrition knowledge, tafher's education level, mother's occupation status, and total member in family were not associated significantly with student"s nutritional status. Recommendations: It suggested that students should be bi-annual weighed continuosly. Teachers or parents should give nutrition education, especially about the importance of breakfast. The cooperation between Ministry of Health and Ministry of National Education needed especially to put nutrition subject formally in elementary school curriculum and to mass media for educating the community. Since decentralization adopted, the local government should pay attention to the economic sector to achieve better economic status of the community and the reach a better purchasing power on quality of food. [Penel Gizi Makan 20061 29(2): 98-106]